Cytokinins - recent news and views of evolutionally old molecules - Sp Chal, Luk X (Functional plant biology, 2012)
Cytokinins (CKs) are evolutionally old and highly conserved low-mass molecules that have been identified in almost all known organisms. In plants, they evolved into an important group of plant hormones controlling many physiological and developmental processes throughout the whole lifespan of the plant. CKs and their functions are, however, not unique to plants. In this review, the strategies and mechanisms of plants - and phylogenetically distinct plant-interacting organisms such as bacteria, fungi, nematodes and insects employing CKs or regulation of CK status in plants - are described and put into their evolutionary context. The major breakthroughs made in the last decade in the fields of CK biosynthesis, degradation and signalling are also summarised.